Pengaruh Pendekatan Teaching Games for Understanding Terhadap Motivasi Belajar dan Keterampilan Lari Sprint pada Mahasiswa - Nopri Abadi Miko; Ashari Efendi; Arda Tonara; Birrul Walidaini (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aimed to analyze the effect of the Teaching Games for Understanding (TGfU) approach on learning motivation and sprint running skills among physical education Students. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 40 students divided into an experimental group and a control group using purposive sampling techniques. Data were collected through a Likert-scale learning motivation questionnaire and a 100-meter sprint skill test. The data were analyzed using paired sample t-test and independent sample t-test after fulfilling the assumptions of normality and homogeneity tests. The results showed significant differences between the experimental and control groups in learning motivation and sprint running skills, with a significance value of 0.000 (p < 0.05). The average learning motivation in the experimental group increased by 17.35, while the control group increased only by 5.35. In sprint running skills, the experimental group improved by 2.10 seconds, whereas the control group improved only by 0.75 seconds. These findings indicate that the TGfU approach is effective in improving student engagement, learning motivation, and motor skills. Therefore, TGfU can be used as an innovative alternative learning model in higher education physical education.